Investigation of High-current Pulsed Electron Accelerator Parameters with Matching Transformer; 13 International symposium on high current electronics - Pushkarev A. I. Aleksandr Ivanovich; Remnev G. E. Gennady Efimovich; Goncharov D. V.; Furman E. G. Edwin Gugovich (Intense electron and ion beams, 2004)
Title from the title-page.